The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.jdiacomp.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anxiety and depression symptoms and cognitive testing and neuroimaging in type 2 diabetes

Abstract: Structured Abstract Aims Anxiety, depression, accelerated cognitive decline, and increased risk of dementia are observed in individuals with type 2 diabetes. Anxiety and depression may contribute to lower performance on cognitive tests and differences in neuroimaging observed in individuals with type 2 diabetes. Methods These relationships were assessed in 655 European Americans with type 2 diabetes from 504 Diabetes Heart Study families. Participants completed cognitive testing, brain magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…The findings of several included studies suggest an association between T2DM and general cognitive deficits [ 30 , 38 , 45 , 47 , 51 ]. Reduced cognitive performance was noticed on different cognitive domains including working memory [ 8 , 30 , 32 , 38 , 45 , 46 , 47 , 48 , 51 ], attention [ 8 , 32 , 46 , 51 ], the speed of information processing [ 38 , 52 ], and executive function [ 8 , 32 , 51 ]. Surprisingly, some studies mainly demonstrated that the cognitive abnormalities may occur at early diabetic stages or may not be noticed even in old patients and after a long duration of illness [ 37 , 38 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings of several included studies suggest an association between T2DM and general cognitive deficits [ 30 , 38 , 45 , 47 , 51 ]. Reduced cognitive performance was noticed on different cognitive domains including working memory [ 8 , 30 , 32 , 38 , 45 , 46 , 47 , 48 , 51 ], attention [ 8 , 32 , 46 , 51 ], the speed of information processing [ 38 , 52 ], and executive function [ 8 , 32 , 51 ]. Surprisingly, some studies mainly demonstrated that the cognitive abnormalities may occur at early diabetic stages or may not be noticed even in old patients and after a long duration of illness [ 37 , 38 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, besides the influence on patients' QOL, research shows that anxiety and depression will change the volume and mean diffusivity of the white and gray matter, which can ultimately result in cognitive disturbance. 38 These findings indicate that healthcare providers should assess psychological and physiological symptoms among patients with chronic diseases, especially for depression and anxiety, since those symptoms are easily neglected by patients and healthcare providers. Future research should not underestimate the impact of depression, anxiety, fatigue, and impaired sleep quality on patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, besides the influence on patients’ QOL, research shows that anxiety and depression will change the volume and mean diffusivity of the white and gray matter, which can ultimately result in cognitive disturbance. 38…”
Section: Discussionmentioning
confidence: 99%
“…Information on risk factors could not be determined for two studies [ 36 , 47 ]. Anxiety and depression are possible modifying factors when assessing cognitive impairment, due to the potential effects these affective disorders have on confounding cognitive testing performance [ 65 ]. One study controlled for depressive symptoms, but cognitive performance was not an outcome of interest [ 37 ].…”
Section: Discussionmentioning
confidence: 99%